A The Indonesia-Malaysia border as a simulacrum of nationalism: A hyperreality study of the Jagoi Babang community in West Kalimantan - Thomy Sastra Atmaja; Bistari; Muhammad Jailani; Nina Ayuni (Jurnal Civics: Media Kajian Kewarganegaraan, 2026)
This article seeks to investigate how simulacra are carried out by Malaysia and the efforts of the border community in Jagoi Babang to maintain their identity with a spirit of nationalism towards Indonesia. Using Baudrillard's theory of hyperreality and simulacra, this study explores how the border community filters various simulacra efforts carried out by Malaysia to change the reality of the border community towards Indonesia. This study uses a case study approach involving observation, documentation, and interviews with 15 informants from various backgrounds. The findings show that Malaysia creates simulacra by giving Indonesian communities in the border region free access to Malaysian state facilities. Meanwhile, the border communities make two efforts to maintain their national identity and avoid being influenced by Malaysian simulacra. First, they strengthen nationalism by using the Indonesian language. Second, they defend their culture through cultural activities and training for the younger generation. The research has theoretical and practical implications because the community has the active ability (agency) to reject simulacra, thereby enriching Baudrillard's theory. In practice, strengthening language and culture at the border is a vital form of non-military national resilience that must be integrated into border policy alongside security and economic approaches.